Legal Consequences of the Annulment of a Decision on Amendment to the Articles of Association for Shareholders in a Limited Liability Company (Case Study of Decision No. 196/G/2019/PTUN-Jkt - Bustari, Muhammad Ilham (Journal Research of Social Science, Economics, and Management, 2025)
Amendments to the Articles of Association of a Limited Liability Company in Indonesia must be carried out through a General Meeting of Shareholders (GMS), notarized in a deed, and approved by the Ministry of Law and Human Rights. The case of PT. Optimalah Mineral in Decision No. 196/G/2019/PTUN. Jkt demonstrates that the annulment of such amendments can have significant impacts on shareholders, underscoring the importance of procedural compliance. This study, using a normative juridical method and case study approach, analyzes the legal consequences of annulling the Ministry’s decree on the Articles of Association and the court’s legal considerations. The findings show that the annulment affects the legal status, ownership, and economic rights of shareholders, while also revealing violations of the general principles of good governance. These results are expected to contribute to the development of corporate and notarial law and serve as a reference for notaries, shareholders, and regulators.